Uma análise dos tipos de registros de representação semiótica utilizados por licenciandos em Matemática no estudo de funções quadráticas - Caçandre, Elemilson Barbosa (2023)
Mathematics, like other disciplines, is the subject of research that establishes a parallel with some theories, in order to strengthen pedagogical action. The Theory of Semiotic Representation Registers (TRRS), created by Raymond Duval, can be used as a support for learning Mathematics, with regard to the representation of its mathematical objects and the teaching and learning process, since the theory determines that understanding is linked to the representation of the mathematical object in more than one type and to the process of transiting between these representations. Amidst the difficulties that students have regarding the study and apprehension of the concept of functions and the importance of the content that interacts with different areas of knowledge, such as the Natural Sciences and their Technologies, and the fact that the teaching of functions is provided by the Mathematics teacher, this research sought to identify the types of semiotic representation records used by Mathematics undergraduates in tasks on quadratic functions. For this, the main objective was to investigate the Semiotic Representation Registers (RRS) used by the licentiate students. The research was carried out with students of the 2nd and 8th periods of the degree course in Mathematics at a Federal Institute of Espírito Santo (IFES), in seven stages, through the application of tasks on quadratic functions, analysis of the types of semiotic registers mobilized by the participants and the moments of socialization of the results in the researched group. It is a qualitative research, participant with interaction between researcher and subjects, throughout the stages. As a data collection instrument, lists of tasks and moments of socialization were used that provided dialogues about the RR used by the undergraduates. Through the results analyzed, it could be seen that students, both in the 2nd and 8th periods, initially did not have a contribution on what is defined as semiotic representations or on the processes of conversion and treatment of records, as they did not represent the mathematical concept in more than one way. It was possible to observe that the students initially registered the quadratic functions primarily through the algebraic record and a few times through the graph, however, after the moment of socialization, the students were more resourceful in the representation of the approached mathematical object, using algebraic records, graphics, tabular, in native language and others. The use of the algebraic register used in the resolution of the proposed tasks was corroborated by the speeches of the participants who indicated that, in the process of teaching Mathematics, they did not have access to the different possibilities of registering the quadratic functions. In this way, when using TRRS in the Mathematics teaching process, whether in undergraduate courses or in continuing education courses with teachers, this can contribute to the improvement of Mathematics learning rates in Brazil, by students of any educational level.